Adverse drug reactions experienced by out-patients taking chlorpromazine or haloperidol at Zomba Mental Hospital, Malawi - Ibrahim Chikowe; McDonald Domingo; Vasco Mwakaswaya; Shagufta Parveen; Chitsanzo Mafuta; Elizabeth Kampira (BMC Research Notes, 2019)
Abstract Objective Drugs for managing mental disorders can cause adverse drug reactions (ADRs) that have negative impacts on patients yet, in Malawi, epidemiological data on the drug-related problems are limited. This study assessed the prevalence and severity of ADRs in out-patients at Zomba Mental Hospital. Results Twenty-six of forty patients (65.0%) were taking haloperidol and 14 (35.0%) chlorpromazine. The commonest diagnosis was schizophrenia (n = 23, 57.5%) followed by epileptic psychosis (n = 4, 10.0%) and general psychosis (n = 4, 10.0%) with one of psychotic depression and one psychosis secondary to general medical condition. Comorbidities were also found with epilepsy being the commonest (n = 4, 10.0%). All patients reported at least one ADR of varying severity (mild, moderate and severe). Polydipsia was the most prevalent (24, 60.0%) followed by weight gain (20, 50.0%), spasm (15, 37.5%) and xerostomia (15, 37.5%). Some ADRs were gender specific and these included impotence (6/27, 29.6%) for males and menstrual changes (3/14, 21.4%) for females. Severe ADRs were more common in the older aged group (> 35 years 8.3% vs 7.1%), in males (11.1% vs 0.0%) and on chlorpromazine (14.3% vs 3.8%). Patients taking chlorpromazine and haloperidol are at risk of experiencing a wide range of ADRs with varying degrees of severity.